(untitled) (Research, Society and Development, 2021)
Chemical looping combustion (CLC) processes have been shown to be promising and effective in reducing CO2 production from the combustion of various fuels associated with the growing global demand for energy, as it promotes indirect fuel combustion through solid oxygen carriers (SOC). Thus, this study aims to synthesize, characterize and evaluate mixed copper and titanium oxide as a solid oxygen carrier for use in combustion processes with chemical looping. The SOC was synthesized based on stoichiometric calculations by the polymeric precursor method and characterized by: X-ray fluorescence (XRF), X-ray diffraction (XRD), Scanning Electron Microscopy (SEM-FEG) with EDS, and Programmed Temperature Reduction (PTR). The oxygen carrying capacity (ROC) and the speed index of the reduction and oxidation cycles were evaluated by Thermogravimetric Reactivity (TGA). The main reactive phase identified was: The CuO phase for the mixed copper and titanium oxide were identified and confirmed by X-ray diffraction using the Rietveld refinement method. The reactivity of the CuO-TiO2 system was high, obtaining a CH4 conversion rate above 90% and a speed index of 40%/min. Due to the structural characteristics and the reactivity tests of this material, it is concluded that mixed copper and titanium oxide have the necessary requirements to be used in chemical looping combustion (CLC) processes.